2020
DOI: 10.19087/jveteriner.2020.21.4.629
|View full text |Cite
|
Sign up to set email alerts
|

Ectoparasites Diversity of Microchiroptera Bats Suborder in Jepang Cave, Plawangan Hill, Sleman, Yogyakarta

Abstract: Ectoparasites in bats can cause a decrease in health and can be a disease vector. Ectoparasites found in bats are generally members of the Insect Class and Arachnida Class. This study was aim to determine the diversity of ectoparasites in bats of the Microchiroptera suborder in Jepang Cave, Plawangan Hill, Sleman, Yogyakarta and knowing various factors that influence the existence of these ectoparasites in bats. Catching bats is done by mist net, bats are anesthetized and morphometric measurements are carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…from Ectopsocidae family (Sari et al, 2015). Meanwhile, research in the Lombok area is still very minimal, recorded two studies, mentioning that there are 3 species of ectoparasites namely Megistopoda aranae, Dermacentor sp., and Nycteribia kolenati (Poerwanto et al, 2020) and mentioning that of the 2 types of bats studied were Macroglossus minimus and Eonycteris spelaea there were 4 types of ticks namely Ixodes sp., Amblyomma sp., Dermacentor sp., and Rhipicephalus sp.…”
Section: Introductionmentioning
confidence: 91%
“…from Ectopsocidae family (Sari et al, 2015). Meanwhile, research in the Lombok area is still very minimal, recorded two studies, mentioning that there are 3 species of ectoparasites namely Megistopoda aranae, Dermacentor sp., and Nycteribia kolenati (Poerwanto et al, 2020) and mentioning that of the 2 types of bats studied were Macroglossus minimus and Eonycteris spelaea there were 4 types of ticks namely Ixodes sp., Amblyomma sp., Dermacentor sp., and Rhipicephalus sp.…”
Section: Introductionmentioning
confidence: 91%
“…Then, we also examined ectoparasites in the body because ectoparasites are disease agents in animals usually found outside the human body, including on the skin's surface and between the hair. Ectoparasites also include parasites that do not remain in the host's body but come and go into the host's body (14). Therefore, we chose these organs and ectoparasites as research samples.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Eucampsipoda bats flies were common on megabats, and they had infested Eonycteris spelaea and Rousettus leschenaultii in Southeast Asia countries (Lim et al 2020;Fajri et al 2018;Azhar et al 2015). Basilia ectoparasites were commonly obtained in megabats and microbats, and Poerwanto et al (2020) reported their presence on Miniopterus schreibersii in Yogyakarta, Indonesia.…”
Section: Ectoparasites Diversitymentioning
confidence: 99%
“…Mite ectoparasites infesting bats in Indonesia were from the Spinturnicidae family, while the ticks were from the Ixodidae and Argasidae families (Fajri et al 2018). Several studies reported ticks and mites ectoparasites infestation on bats in Indonesia (Poerwanto et al 2020;Fajri et al 2018). The results of Meristaspis sp.…”
Section: Ectoparasites Diversitymentioning
confidence: 99%